Prevalence of Anemia and Its Association with Dysmenorrhea Severity Among Female Students: An Epidemiological Study - Winarni; Nukhbatul Bidayati Haka; Lenny Irmawaty Sirait; Raudhatul Munawarah; Mega Octamelia (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Dysmenorrhea refers to menstrual pain frequently encountered by adolescent girls, which can significantly disrupt their daily activities. The severity of dysmenorrhea can be influenced by factors such as anemia and nutritional status. A survey conducted among 46 high school and vocational students revealed that 39 students reported experiencing menstrual pain, while 7 did not. Additionally, students expressed feelings of fatigue, exhaustion, lethargy, and weakness during their menstrual periods.The objective of this study was to investigate the correlation between the occurrence of anemia and the intensity of dysmenorrhea among high school/vocational students. Utilizing an analytical survey method with a cross-sectional design, the study included a population of 306 students, from which a random sample of 73 was selected. Data were gathered using questionnaires. The findings indicated that only a few students suffered from severe dysmenorrhea, yet more than half exhibited signs of anemia. A significant relationship was identified between anemia and the severity of dysmenorrhea among the participants.In conclusion, the study highlights that anemia is associated with increased dysmenorrhea severity. It emphasizes the need for schools to enhance health facilities for female students experiencing dysmenorrhea and to provide education on the importance of reproductive health.